Child Sexual Abuse Whom Trailing into the Crime of Sexual Assault A Case Report - Elbek, Tülay; Erel, Özlem; Dirlik, Musa; Özkök, Selim; Aksu, Hatice; Kallem, Füsun Çallak; Korkmaz, Bedir; Katkıcı, Ufuk (The Bulletin of Legal Medicine, 2016)
Prisons are especially high-risk areas for children because sexual abuse is used for punishment in prisons. We aimed to draw attention to children’s rights by presenting a case of sexual abuse offender who became a sexual abuse victim while in prison because of this crime.In the examination of a 10-year-old boy who was allegedly sexually abused by two people, there were infected fibrous bands, ecchymosis extending to the anus, anal deterioration of symmetry of pleats, mildly decreased anal tone and oval view of anus.A 14-year-old boy was allegedly committed to sexual abuse crime and was arrested. He admitted to our hospital 9 days after the arrest. There were ecchymosis and abbresions on his body. He he claimed that he was beaten by the prisoners in the same ward. Two months later, the same boy admitted to our department and claimed that he was beaten in the toilet and underwent anal rape by putting a pen. There was no clue of beat or rape in the examination. In the psychiatric assessment, he was diagnosed as post traumatic stress disorder.According to the The United Nations Convention on the Rights of the Child, rights of the children are protected by the state. Even in prisons, rights of the children should be protected.In our case, the perpetrator and the victim could not be adequately protected children from sexual abuse, crime and prison environment that is ineffective in the prevention of crime suggests that contribute to prison again.Key Words: Crime, Children’s rights, sexual abuse
Keywords: crime; children’s rights; sexual abuse